Rancang Bangun Mesin Pemecah Kulit Ari Kedelai Untuk Meningkatkan Produktivitas Industri Tempe Pada UMKM Tempe Bapak Mahmudi - Munir, Munir; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Soybeans are an important food ingredient in Indonesia and are the main ingredient in making tempeh. Mr. Mahmudi's tempeh MSME in Sidoarjo has difficulty meeting market demand because the soybean peeling process is still done manually, resulting in slow production and less than optimal results. This study aims to design a more efficient soybean peeling machine and measure productivity increases after its implementation. The design process was carried out through literature studies, field observations, interviews, and data analysis, including worker anthropometric data to ensure the machine is ergonomic and safe to use. Test results showed that the machine was able to peel 8 kg of soybeans in 1 minute 9 seconds, much faster than the manual method which requires 8 minutes 23 seconds. Productivity increased by 628.9%, proving that this machine can significantly improve the efficiency, consistency, and production capacity of MSMEs.